Aquisição de debêntures por fundos multimercados: um estudo considerando a proteção dos credores - Guimarães, Thayse Machado (2018)
Companies financing through debt securities may lead to conflicts of interest between shareholders and bondholders, so this study aims to investigate the influence of bondholders’ protection index in multimarket funds interest through the acquisition of debentures. This survey comprised 926 series of debentures, which represent 61% of the total volume of issued debentures in Brazil from 2009 to 2017. Regarding multimarket funds, 1753 funds were considered, which cover approximately 21.68% of Brazilian multimarket funds total net assets in the same period. In order to test the proposed relationship, we also have considered variables corresponding to characteristics of debentures, issuing companies and multimarket funds. The main evidence indicates that the most common restrictive clauses refer to companies' negligent performance, liquidation, dissolution, and bankruptcy, as well as restrictions on the structure change. Moreover, the less common clauses comprise policy of indebtedness, issuance of shares and amortization, in addition to a downgrading of rating. Concerning bondholders' protection index, analyzed without the weighting of the "automatic maturity" clause and with the weighting by this clause, we have noticed, respectively, averages of 0.6731 and 0.5254. It seems that after weighting, there was a statistically and significant reduction in these index values, at the level of 1%, in the beforementioned period. Concerning allocations of multimarket funds, it was noticed the small participation of debentures in these funds portfolios, since only about 1.36% is invested in debt securities. Furthermore, for testing this study hypothesis, two linear regression models were measured with pooled estimators, applying the standard error correction by White's robust matrix (1980). We point out that the noticed relationships in econometric models respond to the H1 hypothesis at the 1% significance level, which indicates, therefore, that multimarket funds tend to be influenced by bondholders' protection index in the process of corporate bonds acquisition.